The quality of life of epileptic patients - Harsono, Harsono (Faculty of Medicine, Trisakti University, 2008)
Epilepsy has historically been surrounded by prejudice and myth, and associated with many misconceptions. Even today, people with epilepsy experience psychosocial problems, especially in their relationships and employment. Age, seizure severity and frequency, stigma of epilepsy, social deprivation, fear and anxiety, factors responsible for inadequate treatment, treatment gap, and healthcare needs may affect the quality of life of epileptic patients. Improving the diagnosis, treatment, prevention, and social acceptability are important factors in achieving the objective of the management of epilepsy. Treatment of epilepsy refers to any intervention that is intended to restore health status including quality of life. Quality of life is recognized as an important outcome in epilepsy treatment. Quality of life has been reported to vary across epileptic patients with different clinical, demographic, and socio-economic variables. Seizure type and frequency have been found to be significant predictors of quality of life scores. For measuring quality of life in clinical practice, such as in epileptic patients, a wider range of properties is required to ensure that a measure can be used routinely. These include validity, appropriateness and acceptability, reliability, responsiveness to change, and interpretability.